The Effect of Sustainability Disclosure and Corporate Governance on Firm Value: Evidence from Indonesia’s Infrastructure Sector - Febriyan Amuktiningsih; Risky Budianto (Universitas KH. Abdul Chalim Mojokerto, 2026)
This research investigates how sustainability disclosure and corporate governance affect the valuation of infrastructure firms listed on the Indonesia Stock Exchange from 2021 to 2024. Utilizing a quantitative design, it applies panel data regression via the Fixed Effect Model with cross-section weights (EGLS). Drawing from 160 firm-year observations chosen through purposive sampling with defined criteria, key insights emerge, sustainability disclosure negatively impacts firm value, hinting that markets in capital-heavy sectors may not quickly value detailed sustainability reports. Conversely, governance elements like the board of directors, independent board of commissioners, and audit committee exert positive, significant effects on value. Ownership structure, however, lacks notable influence. Overall, these patterns suggest investors prioritize swift governance enhancements over expansive sustainability efforts, especially in infrastructure where heavy investments and extended projects prevail.